Prevalence of and risk factors for tuberculosis among healthcare workers in Chinese tuberculosis facilities - Wang, X; He, T; Geng, M; Song, Y; Wang, J; Liu, M; Hoosdally, S; Cruz, A; Zhao, F; Pang, Y; Zhao, Y; He, G (BioMed Central, 2018)
Background China is one of 22 countries with a high tuberculosis (TB) burden in the world. Healthcare workers (HCWs) have a high risk of contracting Mycobacterium tuberculosis infection due to insufficient infection control practices. We conducted a cross-sectional study to explore the prevalence of TB and its associated risk factors among HCWs in Chinese TB facilities. Methods Two hundred and forty-one TB facilities employing a total of 9663 HCWs were selected from 12 provinces in China to represent healthcare settings at the provincial, prefectural, and county levels. Structured questionnaires were used to collect information on TB infection control practices and HCWs in those facilities. Data was double entered into EpiData 3.1; TB prevalence and associated risk factors were analyzed using SPSS 21.0 with bivariate and multivariate regression models. Results The results showed that 71 HCWs had been diagnosed with TB, accounting for a prevalence of 760/100 000. The multivariate analysis showed that associated risk factors included belonging to the age group of 51 years and above (aOR: 6.17, 95% CI: 1.35–28.28), being a nurse (aOR = 3.09, 95% CI: 1.15–8.32), implementation of 0–9 items of management measures (aOR = 2.57, 95% CI: 1.37–4.80), and implementation of 0–1 items of ventilation measures (aOR = 2.42, 95% CI: 1.31–4.47). Conclusion This was the first national large sampling survey on TB prevalence among HCWs in China. It was found that the implementation of TB infection control practices in some facilities was poor. The TB prevalence in HCWs was higher than that in the general population. Therefore, TB infection control practices in Chinese medical facilities should be strengthened.